Multilayer Membranes of Glycosaminoglycans and Collagen I Biomaterials Modulate the Function and Microvesicle Release of Endothelial Progenitor Cells - Bingyan Dai; Qunwen Pan; Zhanghua Li; Mingyan Zhao; Xiaorong Liao; Keng Wu; Xiaotang Ma (Stem Cells International)
Multilayer composite membrane of biomaterials can increase the function of adipose stem cells or osteoprogenitor cells. Recent evidence indicates endothelial progenitor cells (EPCs) and EPCs released microvesicles (MVs) play important roles in angiogenesis and vascular repair. Here, we investigated the effects of biomaterial multilayer membranes of hyaluronic acid (HA) or chondroitin sulfate (CS) and Collagen I (Col I) on the functions and MVs release of EPCs. Layer-by-layer (LBL) technology was applied to construct the multilayer composite membranes. Four types of the membranes constructed by adsorbing either HA or CS and Col I alternatively with different top layers were studied. The results showed that all four types of multilayer composite membranes could promote EPCs proliferation and migration and inhibit cell senility, apoptosis, and the expression of activated caspase-3. Interestingly, these biomaterials increased the release and the miR-126 level of EPCs-MVs. Moreover, the CS-Col I membrane with CS on the top layer showed the most effects on promoting EPCs proliferation, EPCs-MV release, and miR-126 level in EPCs-MVs. In conclusion, HA/CS and Collagen I composed multilayer composite membranes can promote EPCs functions and release of miR-126 riched EPCs-MVs, which provides a novel strategy for tissue repair treatment.